The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/nau.23489
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐scale DNA methylation study in women with interstitial cystitis/bladder pain syndrome

Abstract: Aims To assess the feasibility of using voided urine samples to perform a DNA methylation study in females with interstitial cystitis/bladder pain syndrome (IC/BPS) as compared to age- and race-matched controls. A unique methylation profile could lead to a non-invasive, reproducible, and objective biomarker that would aid clinicians in the diagnosis of IC/BPS. Methods Nineteen IC/BPS patients and 17 controls were included. IC/BPS patients had an Interstitial Cystitis Symptom Index score of >8; controls had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These affected genes were associated with the glutathione metabolism related to oxidative stress and neuropeptide hormone activity . A genomewide methylation study on voided urine from patients with interstitial cystitis revealed genes downstream of the MAPK pathways were differentially methylated when compared to healthy controls . These studies highlight the epigenetic changes in the target tissues of patients.…”
Section: Epigenetic Mechanisms In Visceral Painmentioning
confidence: 86%
See 1 more Smart Citation
“…These affected genes were associated with the glutathione metabolism related to oxidative stress and neuropeptide hormone activity . A genomewide methylation study on voided urine from patients with interstitial cystitis revealed genes downstream of the MAPK pathways were differentially methylated when compared to healthy controls . These studies highlight the epigenetic changes in the target tissues of patients.…”
Section: Epigenetic Mechanisms In Visceral Painmentioning
confidence: 86%
“…123 A genomewide methylation study on voided urine from patients with interstitial cystitis revealed genes downstream of the MAPK pathways were differentially methylated when compared to healthy controls. 124…”
Section: Evidence For Epigenetic Changes In Patients With Visceral mentioning
confidence: 99%
“…The symptom of frequency or urgency is far more common than that of bladder discomfort 2 . The overall prevalence range of IC/BPS is approximately 2.7%–6.5%, and this disease can cause massive financial costs and severely impair the health‐related quality of life 3 . In addition, IC/BPS is more prevalent in women with an estimated female‐to‐male ratio ranging from 5:1 to 10:1 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2 The overall prevalence range of IC/BPS is approximately 2.7%-6.5%, and this disease can cause massive financial costs and severely impair the health-related quality of life. 3 In addition, IC/BPS is more prevalent in women with an estimated female-to-male ratio ranging from 5:1 to 10:1. 4 To date, the pathophysiology of IC/BPS is still not fully understood and no optimal treatment for this disease has been established.…”
Section: Introductionmentioning
confidence: 99%
“… 8 MAPK is associated with inhibition of cell growth, inflammation, and with mediating apoptosis in different cell types. 9 MAPK and NF-κB are phosphorylated and then activated by many stimuli such as cytokines and cell stress. 10 Activation of MAPK/NF-κB can promote the expression of various pro-inflammatory cytokines, thereby regulating inflammation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%